(untitled) - Võ, Văn Hòe (Hà Nội, 2011)
Khái quát địa lý, lịch sử văn hóa làng Phước Thuận thuộc Thành phố Đà Nẵng ngày nay.
Keywords: Names, Geographical,Tên, địa lý; Vietnam,Đa Nang city,Việt Nam,Thành phố Đà Nẵng